Molecular Mechanisms of Gas Diffusion in CO2 Hydrates - Liang, Shuai; Liang, Deqing; Wu, Nengyou; Yi, Lizhi; Hu, Gaowei (The Journal of Physical Chemistry C, 2016)
Gas diffusion is considered a rate-limiting step in the formation of gas hydrates, yet its molecular 'mechanisms remain unclear. In this work, we present the molecular mechanisms of the CO2 cage-to-cage transport in gas hydrates, as directly observed from molecular dynamics simulations performed at elevated temperatures. We found that at least one water vacancy is required for the CO2 molecules to pass through five-membered water rings, while only the distortion of the local ring structure is required for the CO2 molecules to pass through the six-membered water rings. We used the transition-state theory to estimate the relevant kinetic parameters associated with the CO2 diffusion in gas hydrates. The calculated free energy of activation is about 44 +/- 6 kJ/mol, and the diffusion coefficient is in the range of 1.0 X 10-(16) similar to 2.0 x 10(-14) m(2)/s, for the CO2 diffusion at 270 K, in close agreement with previous experiments. This work suggests that the presence of empty cages is crucial for the CO2 cage-to-cage transport in gas, hydrates.